Potential Anti-inflammatory Sesquiterpene Lactones from Eupatorium lindleyanum - Wang, Fang; Zhong, Huanhuan; Fang, Shiqi; Zheng, Yunfeng; Li, Cunyu; Peng, Guoping; Shen, Xinchun (Planta Medica, 2018)
Eupatorium lindleyanum has traditionally been used as folk medicine in Asian countries for its therapeutic effects on tracheitis and tonsillitis. Investigation of the anti-inflammatory active constituents from E. lindleyanum led to the isolation of two novel sesquiterpene lactones, named eupalinolide L (1) and eupalinolide M (2), and seven known sesquiterpene lactones (3–9). The structures and configurations of the new compounds were determined on the basis of spectroscopic analysis, especially 2D NMR techniques. In vivo experiments showed that the sesquiterpenes fraction significantly reduced mouse ear edema induced by xylene (18.6%, p < 0.05). In in vitro assays, compounds 1–9 showed excellent anti-inflammatory activities, as they lowered TNF-α and IL-6 levels in lipopolysaccharide-stimulated murine macrophage RAW 264.7 cells (p < 0.001). The above results suggest that the sesquiterpene lactones from E. lindleyanum can be developed as novel potential natural anti-inflammatory agents.
Keywords: Eupatorium lindleyanum; Asteraceae; eupalinolide L; eupalinolide M; sesquiterpene lactones; anti-inflammatory activity